1993
DOI: 10.1111/j.1751-1097.1993.tb04975.x
|View full text |Cite
|
Sign up to set email alerts
|

A GARLIC EXTRACT PROTECTS FROM ULTRAVIOLET B (280–320 nm) RADIATION‐INDUCED SUPPRESSION OF CONTACT HYPERSENSITIVITY

Abstract: Lyophilized aged garlic extract has been incorporated at concentrations of 0.1%, 1% and 4% by weight into semipurified powdered diets and fed to hairless mice. Under moderate UVB exposure conditions resulting in 58% suppression of the systemic contact hypersensitivity response in control-fed mice, a dose-responsive protection was observed in the garlic-fed mice; contact hypersensitivity in the UVB-exposed mice fed 4% garlic extract was suppressed by only 19%. If the UVB exposure was replaced by topical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 31 publications
1
33
1
1
Order By: Relevance
“…First, systemic photoimmunosuppression via cis-UCA may depend on oxidative reactions, because a variety of antioxidants have been found to be photoimmunoprotective (15)(16)(17)(18)(19). Thus oxidant states, whether arising as a result of UVB or UVA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, systemic photoimmunosuppression via cis-UCA may depend on oxidative reactions, because a variety of antioxidants have been found to be photoimmunoprotective (15)(16)(17)(18)(19). Thus oxidant states, whether arising as a result of UVB or UVA …”
Section: Discussionmentioning
confidence: 99%
“…Whether ROS play a part in photoimmunosuppression is not clear, although high levels of polyunsaturated fatty acids incorporated into the epidermal lipids certainly predispose hairless mice to immunosuppression by UV radiation (14) and would be a prime source of ROS formation after UV irradiation. Furthermore, photoimmunoprotection by antioxidants such as vitamin E (15), green tea polyphenols (16), garlic (17), carnosine (18), and vitamin C (19), in studies where either UVB or cis-UCA was the immunosuppressive inducer, also suggest that oxidant states play a role.…”
mentioning
confidence: 99%
“…The mechanisms of garlic have been accredited to its effective antioxidant action (Yang et al, 1993), and its ability to stimulate immunological responsiveness (Reeve et al, 1993). Ramakrishna et al (2003) reported that garlic supplementation probably enhanced the activities of the pancreatic enzymes and provided a micro-environment for better nutrient utilisation in rats.…”
Section: General Remarksmentioning
confidence: 99%
“…Many in vitro studies and clinical studies have shown that natural foods or components derived from plants stimulate or regulate the immune response, or exert an anti-stress effect [34]. Immunomodulation effects of garlic have been reported to inhibit the decrease of spleen weight and spleen cell number caused by psychological stress [35], to enhance natural killer activity [36], and to suppress contact hypersensitivity [37]. It is also known that influenza or infection can have a marked effect on the immune system, leading to fatigue.…”
Section: Immunomodulation Effectsmentioning
confidence: 99%